Pulmonary Complications following Cytoreductive Surgery and Perioperative Chemotherapy in 147 Consecutive Patients - Vinicius Preti; David Chang; Paul H. Sugarbaker (Gastroenterology Research and Practice)
Cytoreductive surgery (CRS) with hyperthermic perioperative chemotherapy (HIPEC) has become a treatment option for selected patients with peritoneal metastases (PMs) from gastrointestinal malignancies. The purpose of this study is to evaluate our most recent data regarding pulmonary complications (respiratory distress, pleural effusion, and pneumonia) and attempt to identify risk factors associated with this management plan. This study includes the most recent 4-year experience with appendiceal and colorectal carcinomatosis patients treated in a uniform manner between January 1, 2006 and December 31, 2009. A prospective morbidity and mortality database was maintained and pulmonary adverse events were analyzed with special attention to subphrenic peritonectomy. There were 147 consecutive patients with a mean age of 49.9 years. Fourteen patients (10%) presented grades I–IV pulmonary complications for a total of 26 events. The peritonectomy of right upper quadrant was performed in 74% and right plus left in 49% of the patients. Statistically, there were no more pulmonary complications among patients submitted to peritoneal stripping of right or right and left hemidiaphragm as compared to no subdiaphragmatic peritonectomy (P=1.00 and P=0.58, resp.). In an analysis of 18 quantitative indicators and clinical variables with pulmonary adverse events, only blood replacement greater than six units showed a significant correlation (P=0.0062). Pulmonary adverse events were observed in 10% of patients having CRS and HIPEC. Subphrenic peritonectomy was not a specific risk factor for developing these adverse events.